Analysis Of Land Suitability In Batang Kapas Sub-district, Pesisir Selatan Regency - Nofri Ade; Iswandi Umar (Jurnal Kependudukan dan Pembangunan Lingkungan, 2021)
Population growth affects the increase in land demand for built-up land. Indonesia, which is categorized as a developing country, has the potential to experience a demographic bonus spread throughout the region, not to mention in Batang Kapas sub-district. Batang Kapas Sub-district is one of the areas that have the potential to be affected by the demographic bonus, this is indicated by the increasing demand for building construction and the decreasing use of land in the agricultural sector. The purpose of this study is to provide planning related to the suitability of residential land through a spatial approach with remote sensing technology and geographic information systems. This study uses 6 parameters ranging from digital elevation models to topographic data, flood risk data, and soil characteristics data with the matching method. The results of the study explained that the number of building suitability zones in the unsuitable category reached 0.92% of the total area or 43,958 Ha and for the suitable to very suitable category it was only around 0.05% or a combined area of ​​2624.91 Ha. This condition makes Batang Kapas sub-district one of the areas that cannot be used as a fully residential area, from the conditions of areas prone to flooding to conditions of steep slopes that do not allow for further development so as to minimize the risk of hydrometeorological disasters